Squatting outside the world: notes for an architecture of ethics - Schroeder, Steven (Journal of Architecture and Urbanism, 2014)
Mind takes place in the world, and that matters. We are bodies among bodies, and, no matter what we think, what we do is a matter of where. And thinking about where is a problem for architecture. Richard Luecke’s pithy summary of Aristotle’s Politics was that we go to the city to live but stay to live the good life. The interplay of going and staying takes up a critical theme of Aristotle’s work. To understand the world, he said, we must understand both motion and stasis – not the going alone but the staying that takes place in the middle of it. Luecke took up William James’s figure of perchings in the flight of a bird and put it to work in thinking about cities. The city is a perch for the winged thing we are. To understand our flight, we must also attend to our perching. Aristotle speaks of the city as a place to go and a place to stay, but he also speaks of it as a koinonia turned toward good. That marks it as being human. Aristotle directs our attention to the necessity of the city (we go to live) and to its good (we stay to live the good life). But the staying, the dwelling, is understood within a structure of action: the good is that toward which all things aim. Dwelling, still, we turn. Which qualifies the going, because we are political animals. Going to the city to live, we go nowhere other than where we are. The city is the form of human presence.